Sheeran succeeds in 'Shape of You' music copyright infringement claim. (15th June 2022) - Bosher, Hayleigh
Abstract: This case involved an assessment of UK copyright infringement, including the application of the question of independent creation and substantial similarity in relation to the copying of a musical work.